2021
DOI: 10.1098/rspb.2021.1260
|View full text |Cite
|
Sign up to set email alerts
|

Using the Goldilocks Principle to model coral ecosystem engineering

Abstract: The occurrence and proliferation of reef-forming corals is of vast importance in terms of the biodiversity they support and the ecosystem services they provide. The complex three-dimensional structures engineered by corals are comprised of both live and dead coral, and the function, growth and stability of these systems will depend on the ratio of both. To model how the ratio of live : dead coral may change, the ‘Goldilocks Principle’ can be used, where organisms will only flourish if conditions are ‘just righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 65 publications
0
37
1
Order By: Relevance
“…Experimental studies also revealed that the current speed for optimal food capture is approximately 2 to 6 cm s −1 , while above these values the food capture rate of CWCs is reduced [ 93 , 94 ]. However, as most field observations around thriving CWC reefs measured much higher ambient current velocities (>10 cm s −1 ; [ 25 , 95 98 ] as those experimentally determined, there obviously is a need to study how the coral framework modifies its own local flow environment [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies also revealed that the current speed for optimal food capture is approximately 2 to 6 cm s −1 , while above these values the food capture rate of CWCs is reduced [ 93 , 94 ]. However, as most field observations around thriving CWC reefs measured much higher ambient current velocities (>10 cm s −1 ; [ 25 , 95 98 ] as those experimentally determined, there obviously is a need to study how the coral framework modifies its own local flow environment [ 99 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, flume tank experiments and modeling studies highlighted the remarkable surface roughness of branching corals with large bottom drag coefficients (Monismith, 2007), which significantly slow down bypassing currents, both on colony-and reef-scale (e.g., Chang et al, 2009;Guihen et al, 2013;Johansen, 2014;Lowe and Falter, 2015;Mienis et al, 2019;Bartzke et al, 2021;Hennige et al, 2021). Hence, the baffling capacity of densely distributed coral frameworks on the mound's surface results in a low energy environment allowing fine suspended sediments to settle even under generally turbulent background conditions.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, comparing surface sediments from coral mounds and near-by seafloor settings already revealed a relative enrichment of fine material on the mounds that was assumed to reflect (a) the winnowing of fine sediments from the seafloor next to the mounds and (b) their subsequent deposition on the mounds forced by coral baffling (Mullins et al, 1981;Paull et al, 2000;Wheeler et al, 2011). In addition, experimental and modeling studies have impressively shown how current velocities are reduced within CWC frameworks favoring the settlement of suspended sediments (e.g., Chang et al, 2009;Mienis et al, 2019;Bartzke et al, 2021;Hennige et al, 2021). However, detailed studies on the processes controlling sediment delivery and deposition on coral mounds and their impact on coral mound formation, notably over longer timescales, are still largely lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of a death rule in the model was a significant step to simulating coral growth. In previous work (Hennige et al, 2021), the death rule was fixed at initialisation and it could not be altered or affected by any other aspect of the live simulations. The current proposed model alters the way that the growth and death rules affect the coral particles.…”
Section: Basic Coral Growth Principlesmentioning
confidence: 99%